Effect of applied electric field and electroosmotic flow on biofilm in a microfluidic channel - Siu, Terence Kok Han (2015)
Microfluidics is a multidisciplinary field which involves manipulation of small volumes of fluids in miniaturized systems. These systems are unique platforms to study bacteria/biofilm as the small dimensions accurately represent the microbial environmental conditions. Biofilm has a heterogeneous three-dimensional structure and is formed on moist surfaces with sufficient nutrients. Electroosmotic flow is an electrokinetic phenomenon which has been employed to control and manipulate fluids within a microfluidic system. Both the electrokinetic phenomenon and biofilm have been studied extensively, as two separate topics. A study on the effect of electroosmotic flow on biofilm is reported here as microfluidics presents the potential for the study of biofilms in a controlled environment. Luria Bertani broth was used as the growth medium for Escherichia coli emg2 strain bacteria. Current monitoring method was employed to measure the electroosmotic mobility for varying concentrations of the growth medium in a straight microchannel. The electroosmotic mobility for LB broth without any dilution was found to be negligible. 5% LB broth and PDMS-glass hybrid microchannel were selected for subsequent experiments. The effect of environment temperature on bacteria growth was investigated and found to have negligible influence on the growth rate under these conditions. Under an applied electric field, a large percentage of the bacteria population was significantly displaced in the electroosmotic flow direction, while a small percentage of the bacteria population was displaced opposite to the electroosmotic flow direction. The difference in response can be attributed to the difference in surface charge for each bacterium. This demonstrates an important fact that the surface charge of bacteria of the same type could differ significantly. Electroosmotic flow can potentially be employed to quantify the inhomogeneity of bacteria population in biofilm research.